Characterization of jackfruit straw-based films: effect of starch and plasticizer contents - Mohd Nazri, Muslimah Solehah; Mohamed Amin Tawakkal, Intan Syafinaz; Khairuddin, Nozieana; A. Talib, Rosnita; Othman, Siti Hajar (Universiti Putra Malaysia Press, 2019)
Jackfruit straws are normally disposed as waste by food industries and vendors which may lead to serious environmental issue. In order to reduce the wastage and negative effects to the environment, jackfruit straw waste generated by jackfruit (Artocarpus heterophyllus) shows potential as bio-based film incorporated with starch. This work describes the effect of different starch and plasticizer contents on mechanical and thermal properties of jackfruit straw powder (JSP)/starch films. Film-forming solutions were prepared and cast by mixing JSP with tapioca starch at different ratios and for the plasticized films, ca. 15 - 40% of plasticizers including sorbitol and glycerol were incorporated into the JSP/starch films respectively. The tensile strength and modulus of JSP/starch films pronouncedly increased with increasing starch content, accompanied with a slight decreasing in the elongation at break. The result demonstrated that starch interacted with JSP, resulting in the formation of a new network to improve the properties of JSP films. FTIR spectrum analyses demonstrated the presence of hydrogen bonding in the JSP/starch film. The tensile strength of the plasticized JSP/starch films decreased with increasing sorbitol and glycerol content from 15% to 40%. However, the plasticizing effect of sorbitol became more significant than glycerol, particularly on the tensile properties and thermal stability. Thermal analysis by thermogravimetric showed an increment in the decomposition temperature with the addition of plasticizers into JSP/starch films. The results suggest that films containing JSP and starch have the potential for the development of edible food packaging materials.